Let the music play! : harnessing the power of music for history and social studies classrooms - Pellegrino, Anthony Michael; Lee, Christopher Dean (Emerald Publishing Limited : Information Age Pub., 2012)
LET THE MUSIC PLAY! Harnessing the Power of Music for History and Social Studies Classrooms provides readers an accessible introduction to employing music in history and social studies classrooms. Teachers who wish to develop lessons using music as a resource will find coverage of the significant relationship between music and social studies, pedagogical models designed to facilitate using music within history and social studies lessons, and coverage of salient historical themes in which music has been integral.The book begins by establishing the connection between music and social studies themes. Here readers will explore the ways musicians have attempted to address social, political or historical events and issues through song. Through relevant research and exclusive interviews done for this book, the thoughts of prominent musicians noted for songs promoting social consciousness and selfawareness - including Ian MacKaye, Henry Rollins and Aaron Bedard-are shared. The views of teachers and students in terms of the connections between music and the social studies as well as their inclinations to using music in social studies classrooms are also prominently addressed. Additionally, the book furnishes readers with a practical guide to using music in the social studies classroom. Through explanation of four models for using music in the classroom, readers gain relevant ideas useful for a wide variety of instructional methodologies. And finally, the authors delve into three of the most enduring themes in American history and social studies curricula: race, labor and class. Through an examination of these topics, within the framework of music, readers are given the opportunity to discern the way music has manifested in each of these topics. Readers will also enjoy lesson plans and annotated playlists associated with each of these topics.
Keywords: Music in education.; History -- Study and teaching.; Social sciences -- Study and teaching.; Music -- Social aspects.; Music -- Political aspects.; Education -- History.; Teaching skills and techniques.; History of education.; elektronické knihy; electronic books